(3EOGQI GdCYeGd hab efXhQ eYGUQ (B/s - (3YHGS, GfS YHO GdHGSWs ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2011)
(3eaghe h CgejI GdGOGQI h GdMGLI GdjgG , eLGdGJ GdGOGQI , TehdjI GdGOGQI h YehejJgG , YdGbI GdGOGQI HGdYdhe GdGNQi , CKQ GdGOGQI Ydi GdYdhe GdGNQi , eOGQS GdacQ GdGOGQj , GdGOGQI HGdefXhQ GdGSdGej h GdGOGQI aj GdOhd GdfGejI , GdhXGFa GdGOGQjI (B: (3GdJNWjW , GdJfXje , GdJhLjg h GdQbGHI , hXGFa GdefXeI (B: (3GOGQI GdehGQO GdHTQjI , GOGQI GdeTJQjGJ h GdeNGRf , , GOGQI GdGfJGL h GdYedjGJ , GOGQI GdYdGbGJ GdYGeI , GOGQI GdJShjb h GdGOGQI GdeGdjIs
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdEOGQI GdYGeIs